Nondestructive Load Testing and Comparison of Approaches for Bridge Load Rating Using ASD, LFD, and LRFD Methods. - Iplikcioglu, Merve. (2017)
Abstract: The Powder Mill Bridge in Barre, Massachusetts (Vernon Avenue over Ware River, Bridge No. B-02-012 was instrumented during construction and diagnostic load tests were performed. Bridge load ratings were calculated using the Allowable Stress Design, Load Factor Design, and Load and Resistance Factor Design methods with four different approaches. Initially, the rating factors of the Powder Mill Bridge were calculated by hand. The second approach used the bridge load rating program Virtis 6.3, developed by the American Association of State Highway and Transportation Officials, and the results were compared with the hand calculations. The third approach consisted of using the data collected during the diagnostic load tests to modify the load rating factor calculated by hand. The diagnostic load test data was also used to calibrate a finite element model of the Powder Mill Bridge. Finally, the fourth approach used a calibrated finite element model to determine load rating factors of Powder Mill Bridge. The rating factors obtained by using nondestructive test data and the finite element model were higher than the conventional load rating factor since both of these methods take advantage of the true three dimensional system behavior of the structure. The comparison and explanation of the aforementioned methods for calculating rating factors provide bridge owners with insight into the different approaches for calculating bridge load rating factors for maintenance and management decisions.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Civil Engineering.; Advisor: Masoud Sanayei.; Committee: Brian Brenner, Erin Bell, and Gregory Imbaro.; Keyword: Civil engineering.